2012
DOI: 10.1007/s12041-012-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of intersubspecific molecular genetic map of lentil based on ISSR, RAPD and SSR markers

Abstract: Lentil (Lens culinaris ssp. culinaris), is a self-pollinating diploid (2n = 2x = 14), cool-season legume crop and is consumed worldwide as a rich source of protein (~24.0%), largely in vegetarian diets. Here we report development of a genetic linkage map of Lens using 114 F(2) plants derived from the intersubspecific cross between L 830 and ILWL 77. RAPD (random amplified polymorphic DNA) primers revealed more polymorphism than ISSR (intersimple sequence repeat) and SSR (simple sequence repeat) markers. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 41 publications
3
34
3
Order By: Relevance
“…In another study, transferrable SSR markers were also highly polymorphic in lentil (Datta et al 2011). However, in contrast to this, Gupta et al (2012) identified only 4.43 % SSR markers polymorphic. It was because they screened SSR markers only in two genotypes and used agrose gel for separation of PCR amplified product.…”
Section: Discussioncontrasting
confidence: 68%
“…In another study, transferrable SSR markers were also highly polymorphic in lentil (Datta et al 2011). However, in contrast to this, Gupta et al (2012) identified only 4.43 % SSR markers polymorphic. It was because they screened SSR markers only in two genotypes and used agrose gel for separation of PCR amplified product.…”
Section: Discussioncontrasting
confidence: 68%
“…The DNA-based markers, such as RFLP (Havey and Muehlbauer, 1989;Muench et al, 1991;Rajora and Mahon, 1994), RAPD (Sharma et al, 1995;Ferguson et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009;Tewari et al, 2012), AFLP (Sharma et al, 1996;Zavodna et al, 2000;Duran and Perez de le Vega, 2004;Kahraman et al, 2004;Rubeena et al, 2006;Fiocchetti et al, 2009;Toklu et al, 2009), microsatellite markers (Duran and Perez de le Hamwieh et al, 2009;Liu et al, 2008;Babayeva et al, 2009;Reddy et al, 2010;Gupta et al, 2012, Tewari et al, 2012Zaccardelli et al, 2012), inter simple sequence repeat (ISSR) (Zavodna et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009), internal transcribed spacers (ITS) (Fernandez et al, 2000;Mayer and Bagga, 2002;Sonnante et al, 2003), non-transcribed spacer (NTS) (Fernandez et al, 2005), sequenced tagged microsatellite site (STMS) (Inder et al, 2008;Datta et al, 2011), single-nucleotide polymorphisms (SNPs) (Alo et al, 2011), and resistance gene analogue (RGA) (Yaish et al, 2004;Sari et al, 2013) were used to analyze phylogenetic relationships among taxa in the genus Lens, as well as the genetic diversity of cultivated lentil.…”
Section: Genus Lens Millermentioning
confidence: 99%
“…DNA markers are effective tools in evaluating genetic diversity (Fernandez et al, 2002;Phong et al, 2011), constructing genetic maps (Gupta et al, 2012), and molecular identification and classification (Fernandez et al, 2002). Random amplified polymorphic DNA (RAPD) (Williams et al, 1990) and inter-simple sequence repeat (ISSR) (Zietkiewicz et al, 1994) markers are polymerase chain reaction (PCR)-amplified approaches to acquire the genetic information of populations or individuals.…”
Section: Introductionmentioning
confidence: 99%